The Influence of Digital Marketing and Brand Awareness Onpurchase Decisions at the Nino 911 Startup in Medan City - Soterniat Zai; Amrin Mulia Utama Nasution (Sean Institute, 2025)
This research aims to determine the influence of digital marketing and brand awareness on purchasing decisions at the Nino 911 application start-up in Medan City. This research uses quantitative and associative methods. The total population is 425,976 residents spread across 5 sub-districts as representatives of Medan City. In determining the sample, the author used Slovin's theory with a sample of 100, and the sample collection technique used was nonprobability sampling and snowball sampling to determine the sample. The data analysis technique uses multiple linear regression analysis. Based on the research results, it shows that (1) digital marketing variables have a significant influence on purchasing decisions at the Nino 911 start-up in Medan City, (2) brand awareness variables have a significant influence on purchasing decisions at the Nino 911 start-up in Medan City, and (3) digital marketing variables and brand awareness simultaneously have a significant influence on purchasing decisions at the Nino 911 start-up in Medan City.